Shameless. The complete tenth season [videorecording (DVD)]. - Macy, William H., 1950-; White, Jeremy Allen; Cutkosky, Ethan, 1999- (Warner Bros. Home Entertainment, 2020)
The tenth season picks up six months after last season's finale: Frank uses his leg injury to collect as many prescription drugs as possible and his exploits lead him to an old friend.